(untitled) - Anderson, Kenneth (Cambridge, 2004)
Study Speaking is for intermediate level and above students who need to speak English in connection with their academic work. It is intended primarily for use on language programmes preparing learners of English for study at university or college. The course is designed to improve students' speaking skills by: * activating and extending their linguistic competence * increasing their confidence in using spoken English * developing their ability to analyse and evaluate spoken performance * sharpening their strategic competence in face-to-face interaction. Study Speaking is part of a the Study Skills series
Keywords: english language,english language; study and teaching (Higher),foreign speakers,spoken English,problems, exercises, etc